Exercise during energy restriction mitigates bone loss but not alterations in estrogen status or metabolic hormones. Issue 9 (September 2016) - Metzger, C.; Baek, K.; Swift, S.; Souza, M.; Bloomfield, S.
Abstract Summary Energy restriction causes bone loss, increasing stress fracture risk. The impact of exercise during energy restriction on bone and endocrine factors is examined. Exercise with energy restriction did not influence endocrine factors, but did mitigate some bone loss seen with energy restriction in sedentary rats. Introduction Chronic dietary energy restriction (ER) leads to bone loss and increased fracture risk. Strictly controlled trials of long-term ER with and without vigorous exercise are required to determine whether exercise loading can counterbalance ER-induced bone loss. The aim of this current project is to elucidate the impact of exercise and ER on bone mass, estrogen status, and metabolic hormones. Methods Twenty-four virgin female Sprague-Dawley rats (n = 8/group) were divided into three groups—ad libitum fed + exercise (Adlib + EX), 40 % energy restricted + exercise (ER + EX), and 40 % energy restricted + sedentary (ER + SED). Energy availability between ER groups was equal. Treadmill running was performed 4 days/week at 70 % VO2max for 12 weeks. Results Fat and lean mass and areal bone mineral density (aBMD) were lower after 12 weeks (p < 0.05) for ER + EX vs Adlib + EX, but ER + EX aBMD was higher than ER + SED (p < 0.0001). Serum leptin and a urinary estrogen metabolite, estrone-1-glucuronide (E1G), were lower at week 12 (p = 0.0002) with ER, with no impact of exercise. Serum insulin-like growth factor I (IGF-I) declined (p = 0.02) from baseline to week 12 in both ER groups. ER + EX exhibited higher cortical volumetric bone mineral density (vBMD) at the midshaft tibia (p = 0.006) vs ER + SED. Conclusion Exercise during ER mitigated some, but not all, of the bone loss observed in sedentary ER rats, but had little impact on changes in urinary E1G and serum IGF-I and leptin. These data highlight the importance of both adequate energy intake and the mechanical loading of exercise in maintaining bone mass.